Réponses

Meilleure réponse !
2014-05-17T10:16:25+02:00
Bonjour,

Ex 1

1)
On développe.
A = \left(x+3\right)\left(4x+9\right) + \left(x+3\right)\left(2x-5\right)\\
A = \left(4x^2+21x+27\right) +\left(2x^2+x-15\right)\\
A = 6x^2+22x+12

2)
On développe pour tomber sur A.
\left(x+3\right)\left(6x+4\right) = 6x^2+22x+12 = A

3)
a)Forme développée.
A = 6x^2+22x+12\\
A = 6\times 2{,}5^2 +22\times 2{,}5+12\\
A = 104{,}5

b)Forme développée.
A = 6x^2+22x+12\\
A = 6\times 0^2+22\times 0 +12\\
A = 12

c)Forme factorisée (cette valeur annule un des facteurs).
A = \left(x+3\right)\left(6x+4\right)\\
A = \left(-3+3\right)\left(-3\times 6+4\right)\\
A = 0

d)Idem.
A= \left(-\frac 32+3\right)\left(-\frac 32 \times 6+4\right)\\
A  = \left(-\frac 32+3\right)\times 0\\
A  = 0

Ex 2
B = 5^4 \times 4^2\times 2^4\\
B = 5^4\times \left(2^2\right)^2 \times 2^4\\
B = 5^4\times 2^4\times 2^4\\
B = \left(5\times 2\right)^4 \times 2^4\\
B = 10^4\times 16\\
B = 160000

C = 0{,}5^3\times 8{,}9^1\times 2^3\\
C = \left(\frac 12\right)^3 \times 8{,}9 \times 2^3\\
C = 2^{-3}\times 8{,}9 \times 2^3\\
C = 8{,}9

D= 8^9\times 7^2 \times 0{,}125^9\\
D = 8^9 \times 7^2 \times \left(\frac 18\right)^9\\
D = 8^9\times 7^2 \times 8^{-9}\\
D = 7^2\\
D = 49

E = 90^2 \times 5^{-2} \times 2^{-2}\\
E = \left(9\times 10\right)^2 \times \left(5\times 2\right)^{-2}\\
E = 9^2 \times 10^2 \times 10^{-2}\\
E = 9^2\\
E = 81

Si tu as des questions, n'hésite pas ! =)